Pengaruh Budaya Organisasi dan Pengembangan Karier terhadap Kinerja Karyawan pada PT Sinergi Aitikom Kota Jakarta Selatan - Radika Putri Andini; Muhammad Gandung (Jurnal Manajemen Bisnis Era Digital, 2025)
This research aims to determine the influence of organizational culture and career development on employee performance at PT Sinergi Aitikom, South Jakarta City, both partially and simultaneously. This study uses quantitative methods. The population is all 81 employees. Sampling uses saturated sampling techniques. The analysis methods used are validity testing, reliability testing, classical assumption testing, multiple regression analysis, correlation coefficient analysis (r), determination coefficient analysis and hypothesis testing t-test, f-test. The results show that organizational culture (t-value 7.597> t-table 1.990; sig. 0.000 <0.05), this means that organizational culture partially influences employee performance. Career development (t-value 8.932> t-table 1.990; sig. 0.000 <0.05), this means that career development partially influences employee performance. The f test shows the calculated f value (244.849 > f table 3.11; sig. 0.000 < 0.05), simultaneously organizational culture and career development influence employee performance. The coefficient of determination is 0.859, meaning that 85.9% of the influence between organizational culture and career development simultaneously on employee performance is 85.9%. While the remaining (100-85.9% = 14.1%) is influenced by other variables not studied.